PARICALCITOL INHIBITS WNT/?-CATENIN SIGNALING PATHWAY AND AMELIORATES DERMAL FIBROSIS BLEOMYCIN INDUCED SCLERODERMA MODEL - Duran, F.; Yildirim, A.; Yolbas, S.; Ozercan, I. H.; Onalan, E.; Koca, S. S. (Bmj Publishing Group, 2015)
[Abstract Not Available]